Pelatihan Kewirausahaan bagi Pelaku UMKM di Desa Labulanda Kabupaten Buton Utara - Acoci Acoci; Safiudin Safiudin; Asrita Asrita; Wa Ode Nur Fitasari; Nurafni Nurafni (Perkumpulan Kualitama Edukatika Indonesia, 2022)
Empowerment of Micro, Small and Medium Enterprises aims to support initiatives in implementing micro small and medium enterprises. Thus, increasing the income of low- and middle-income people, and creating jobs. However, the existing Micro, Small and Medium Enterprises, especially in Labulanda Village, West Kulisusu District, and North Buton District, have not been able to reduce the unemployment rate. So that entrepreneurship training is needed for Micro, Small and Medium Enterprises in Labulanda Village, North Buton Regency. The method and implementation of this activity include conducting training discussions and coordination first with the Lurah as the partner in charge, then holding a conference to discuss the implementation and goals of the local community. For Micro, Small and Medium Enterprises, this service provides marketing and entrepreneurship training in Labulanda Village, West Kulisusu District, North Buton Regency. The results of this activity show how to assess the effectiveness of the overall training program. Indicators of the success of training activities show that 80% of participants can understand business strategies, entrepreneurial tactics, and product marketing aimed at consumers.